Meneropong Nilai Religius Islam dan Nilai Moral dalam Tradisi Begalan yang Berkembang di Karesidenan Banyumas - Kamaludin, Mustofa; BS, Abdul Wachid (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
The Banyumasan Begalan traditional ceremony is a form of ritual as well as a performing arts entertainment media in the form of drama because there is an element of dialogue in it. From the time sequence of the performances, the utterances, and the tools carried in Begalan have a moral meaning and Islamic religious values in relation to the formation of a Muslim family, namely the realization of the sakinah family, mawadah wa rahmah. Therefore, the Banyumas Begalan traditional ceremony is very suitable as a source of character education in schools and the meaning contained in it can be used as a reference for prospective brides in pre-marriage courses or what we have been managing with Suscatin (Candidate Bride Course).This study aims to describe: (1) the procession of the Begalan tradition, (2) the public's perception of the symbolic meaning, (3) a review of Islamic law and, (4) the function of Begalan. This research is descriptive qualitative. The data collection technique in this research is observation through secondary data, namely in the form of youtube videos, and document review. The object of this research is religious values and moral values in the Begalan traditional ceremony in the former Banyumasan Residency.